The Representation of Skepticism in Don’t Look Up Film: An Overview of Current Environmental Issue - Halim, Nur Mutmainna; Taufik, Muhammad; Fisdarnianti, Fisdarnianti (Indonesian Journal of English Language Studies (IJELS), 2024)
This article explores the representation of skepticism in the film "Don't Look Up," highlighting its commentary on contemporary environmental issues. Through a satirical lens, the film portrays the tension between scientific evidence and societal indifference, revealing the complexities of public perception regarding climate change and ecological crises. The purpose of this study is to analyze the signs that represent skepticism in the film. This type of research is descriptive qualitative research using the semiotic theory of Pierce (1906) which consists of representation (sign), object, and interpretation. The researchers found types of representation in the form of 3 types of quali-sign, 15 sin-sign, and 2 legi-sign. The objects in the form 4 types of icons, 13 types of indexes, and a symbol. The interpretation in the form 17 of argument type. The signs that represent skepticism can be found in scenes in the form of dialogue, attributes, movements, and expressions. The film also represented that skepticism has a negative side towards the environment. In addition, this film represents that skepticism can be carried out in all aspects of social circles such as government, media, and society. The film serves as a critical reflection of current attitudes toward environmental challenges, emphasizing the dangers of misinformation and the necessity for collective action. Ultimately, this exploration underscores the film's relevance in stimulating discourse on the urgent need for recognition and response to the climate crisis, encouraging audiences to reconsider their roles in fostering awareness and advocacy in the face of skepticism.